Variety, Employment and Regional Development in The Netherlands - Koen Frenken; Frank Van Oort; Thijs Verburg; Ron Boschma (European Regional Science Association (ERSA), 2004)
We explain employment growth in 40 Dutch regions for the period 1996-2002. Our main interest is to test the effect of sectoral variety using data on five-digit sector employment, while controlling for traditional variables. Our measure of variety is entropy, as this measure allows for decomposition of variety into related and unrelated variety. We distinguish between related and unrelated variety effects. Related variety is associated with Jacobs externalities (spillovers), while unrelated variety tests portfolio advantages. We also take into account the effect of specialisation on employment growth. The results suggest that only related variety significantly contributes to employment growth. The popular dichotomy between variety and specialisation may thus be misleading. Our study underlines the more recent concept of “diversified specialisations” as central driver of growth.
Keywords: 330